1978
DOI: 10.1192/bjp.132.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid (GABA) in the CSF of Schizophrenic Patients Before and After Neuroleptic Treatment

Abstract: Gamma-aminobutyric acid (GABA) levels in the CSF were measured in 9 normal individuals, 17 drug-free schizophrenic patients and 10 of these same schizophrenic patients after neuroleptic treatment. There was no significant difference between CSF level of GABA in the control group compared to those in schizophrenic patients; however, 6 of the 7 lowest GABA levels were from schizophrenic patients. There was a significant decline of 12 per cent in mean GABA levels in the CSF after a mean of two months of neurolept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…An increase in CSF GABA levels has been found after 30 d treatment with sulpride and to be correlated with long-term neuroleptic treatment . However, Lichtshtein et al (1978) noted a small but significant decrease in CSF GABA levels after 2 months of neuroleptic treatment while Gattaz et al (1986) observed no change in free CSF GABA levels in schizophrenic patients after 3 months of haloperidol treatment. Lastly, Zander et al (1981) reported that stopping chronic anti-psychotic medication treatment produced no change in CSF GABA levels.…”
Section: Csf Studiesmentioning
confidence: 91%
“…An increase in CSF GABA levels has been found after 30 d treatment with sulpride and to be correlated with long-term neuroleptic treatment . However, Lichtshtein et al (1978) noted a small but significant decrease in CSF GABA levels after 2 months of neuroleptic treatment while Gattaz et al (1986) observed no change in free CSF GABA levels in schizophrenic patients after 3 months of haloperidol treatment. Lastly, Zander et al (1981) reported that stopping chronic anti-psychotic medication treatment produced no change in CSF GABA levels.…”
Section: Csf Studiesmentioning
confidence: 91%
“…This is at variance with data reported in the literature. Lichtshtein et al (1978) found a small but significant decline in mean CSF GABA levels in 10 schizophrenic patients after 2 months of neuroleptic treatment, whereas Zimmer et al (1980) reported a significant increase of GABA in 13 schizophrenics after 30 days on sulpiride.…”
Section: Discussionmentioning
confidence: 91%
“…This suppressive effect of HAL on GABA is in agreement with several clinical and experimental studies. A CSF study in schizophrenic patients has demonstrated a significant decline of 12% in mean GABA levels in CSF after -2 months of neuroleptic (chlorpromazine, perphenazine or fluphenazine) treatment (Lichtshtein et al, 1978). From animal studies, Kim and Hassler (1975) reported that 1 h after a single injection of HAL (10 mg/kg) there was a significant decrease in GABA content in tissue homogenates of rat striatum (37%) and substantia nigra (19%), respectively.…”
Section: Effects Of Carbamazepinementioning
confidence: 98%